miR-199a Is Upregulated in GDM Targeting the MeCP2-Trpc3 Pathway - Guan, Chun-Yi; Cao, Jing-Li; Zhang, Lu; Wang, Xue-Qin; Ma, Xu; Xia, Hong-Fei (Frontiers in Endocrinology, 2022)
Gestational diabetes mellitus (GDM), the most common medical pregnancy complication, has become a growing problem. More and more studies have shown that microRNAs are closely related to metabolic processes. The purpose of this paper is to investigate the role of up-regulation of miR-199a-5p expression in GDM. We found that miR-199a-5p was significantly up-regulated in the placenta of GDM patients compared with normal pregnant women, and expressed in placental villi. miR-199a-5p can regulate the glucose pathway by inhibiting the expression of methyl CpG-binding protein 2 (MeCP2) and down-regulating canonical transient receptor potential 3 (Trpc3). This suggests that miR-199a-5p may regulate the glucose pathway by regulating methylation levels, leading to the occurrence of GDM.